The Dialectic of Islam Nusantara and Globalization: The Transformation of Nahdlatul Ulama’s Religious Practices - Bangkit Saputra (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2026)
This study examines the dialectical relationship between Islam Nusantara and globalization through Homi K. Bhabha's Hybridity Theory, focusing on the transformation of Nahdlatul Ulama’s (NU) religious practices within Indonesian modernity. Utilizing a library research methodology, the paper analyzes how traditional Islamic organizations navigate between preserving local traditions and adapting to global influences. The findings reveal that NU employs a sophisticated cultural negotiation strategy, creating a “third space” where new hybrid identities emerge. Through cultural translation, traditional Islamic values are reinterpreted for modern contexts without losing their essence. Furthermore, NU’s approach exhibits an ambivalence that simultaneously accepts and rejects various aspects of globalization. This hybridity enables the organization to maintain its traditional roots while constructively engaging with contemporary challenges, fostering innovative religious practices that blend local wisdom with global perspectives. Studi ini mengkaji hubungan dialektis antara Islam Nusantara dan globalisasi melalui Teori Hibriditas Homi K. Bhabha, dengan fokus pada transformasi praktik keagamaan Nahdlatul Ulama (NU) dalam konteks modernitas Indonesia. Menggunakan metode penelitian kepustakaan, artikel ini menganalisis bagaimana organisasi Islam tradisional bernavigasi antara melestarikan tradisi lokal dan beradaptasi dengan pengaruh global. Temuan menunjukkan bahwa NU menerapkan strategi negosiasi budaya yang canggih, menciptakan